ANALISIS PENGGUNAAN SARANA DAN PRASARANA UNTUK MENUNJANG KEGIATAN BELAJAR MAHASISWA DI UNIVERSITAS PGRI PALEMBANG TAHUN AKADEMIK 2016/2017 - Dian Lestari, Neta; Agus Yusmiono, Boby (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2018)
The benefits of educational facilities greatly affect the smoothness and sustainability of the learning process. Universitas PGRI Palembang has good facilities and infrastructure ranging from comfortable lecture room and has been completed by infocus, accredited library A and integrated lab, and other facilities that support the student learning process, but sometimes facilities that have been maximally completed by University is not in good use by students or by lecturers. This research aimed at investigating the value of benefit from the use of facilities and infrastructure to support the student learning activities in academic year 2016/2017. This research was descriptive by using quantitative approach. The result concluded that the infrastructure facilities in Universitas PGRI Palembang in good categories which were seen from the number of student statement 80,20.